Literasi Saintifik Berdasarkan Kecerdasan Majemuk dan Motivasi Belajar - Adib Rifqi Setiawan (Universitas PGRI Semarang, 2019)
Burhān al-Dīn al-Nu’mān ibn Ibrōhīm al-Zarnūjī in his treatise entitled “Ta'līm al-Muta'allim Ṭorīq al-Ta'allum” informed that the academic achievement has six things dependency: ingenious acumen, fervent desire, resilience, sufficent sustenance, guidance of a teacher, and length of time. Based on this perspective, we was empirically tested students scientific literacy through correlational research. In particular, first, multiple intelligences was examined based on Multiple Intelligences Survey (MIS). Second, science learning motivation was explored used Science Motivation Questionnaire II (SMQ-II). Third, scientific literacy was tested that focused on competence domain and environmental content. The participants of the study were 128 students in Kabupaten Kudus choosen by random sampling technique. We used Pearson r to elaborate relation of scientific literacy with each type of multiple intelligences nor component of science learning motivation. It reveals that naturalistic intelligence and self-efficacy has strong correlation with scientific literacy. The findings suggest that it is important to facilitate students’ intelligence and motivations to guide them on achieving scientific literacy.